The fields - Richter, Conrad, 1890-1968 (A. A. Knopf, 1946)
Continues the saga of Sayward Luckett Wheeler, who marries the educated New Englander, Portious, and bears him eight children. As pioneer, wife, and mother, she struggles to create a home in the wilderness for her family. The second novel of Conrad Richter's trilogy including The trees and The town."